2015
DOI: 10.1007/s10689-015-9828-6
|View full text |Cite
|
Sign up to set email alerts
|

Screening of RET gene mutations in Chinese patients with medullary thyroid carcinoma and their relatives

Abstract: The rearranged during transfection (RET) gene is a proto-oncogene; active mutations frequently occur in medullary thyroid carcinoma (MTC). This study investigated the spectrum of germline RET mutations and clinical features in Chinese hereditary MTC patients. A total of 53 family members from 11 different hereditary MTC families were recruited for detection of RET exon 8, 10, 11, 13, 14, 15, and 16 mutations, in genomic DNA from peripheral blood leucocytes using polymerase chain reaction (PCR) and direct DNA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Codon 634 mutations have been reported as the most predominant in several European ( Table 3 ) ( 6–14 ) and non-European series ( Table 4 ) ( 17–25 ). This might be explained by earlier onset of disease and a presentation frequently involving the full-blown MEN2 syndrome (MTC, PHEO, and HPTH).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Codon 634 mutations have been reported as the most predominant in several European ( Table 3 ) ( 6–14 ) and non-European series ( Table 4 ) ( 17–25 ). This might be explained by earlier onset of disease and a presentation frequently involving the full-blown MEN2 syndrome (MTC, PHEO, and HPTH).…”
Section: Discussionmentioning
confidence: 99%
“…Codon 634 mutations are reported as the most prevalent in both European ( 6–16 ) and non-European families ( 17–25 ). However, a recent Greek study of 58 RET positive families found mutations of codon 533 to be predominant ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the majority of MEN 2B patients presented clinical manifestations in the second decade of life and needed to have a total thyroidectomy when they were initially diagnosed [8]. Particularly in this patient, the same mutation was not detected in his mother nor had a history of medullary carcinoma been detected in his paternal or maternal relatives, suggesting that this mutation occurred de novo , which is a relatively common finding, as approximately 75% of MEN 2B patients have de novo RET mutations [22]. …”
Section: Discussionmentioning
confidence: 99%
“…In 85% of MEN2A patients, RET codon 634 (p.Cys634Arg) has been reported as the most prevalent in European and non-European families [18,20,26]. Several other smaller and larger multicenter studies mainly from groups around Europe demonstrated codon 533 as the prevailing in Greece [27], 611 in Portugal and Denmark [28,29], 618 in Cyprus [15], 790 in Germany [18] and 804 and 891 in Italy [19].…”
Section: Discussionmentioning
confidence: 99%